The environmental education policy initiative: Reflections on the process - Alistair Clacherty (Environmental Association of Southern Africa, 1993)
This paper describes aspects of the Environmental Education Policy Initiative (EEPI), as it is now known, with the purpose of reflecting on it and drawing out some key features. Commonly, a process such as the EEPI runs its course with little attempt to reflect more deeply on the process and learn from it. This short paper is intended as a useful learning opportunity for us all.